Night in old Mexico - Aragon, Emilio 1929-; Wittliff, William D.; Duvall, Robert; Irvine, Jeremy 1990-; Cepeda, Angie 1974-; Tosar, Luis; Cosio, Joaquin; Mala Fe.; Omedes, David; Salcedo, Jose; Ramsey, Van Broughton; Johnston, E; et al. (Fort Mill, SC : Phase 4 Films, 2014)
"Forced to give up his land and home, Texas rancher Red Bovie is not about to retire quietly in a trailer park. Instead he jumps in his Cadillac and hits the road with his estranged grandson for one last wild adventure filled with guns, women and booze. It's just another night in old Mexico"--Container insert.
"Forzado a dejar su tierra y su hogar, el vaquero tejano Red Bovie no esta listo para retirarse y vivir en una casa rodante. En vez de ello comienza a conducir su Cadillac en la carretera acompanado por su nieto en una ultima aventura llena de armas, mujeres y bebida. Una noche mas en el Viejo Mexico."--Container insert.
Special features: behind the scenes; theatrical trailer.
Originally produced as a motion picture in 2013.
Director of photography, David Omedes ; edited by Jose Salcedo ; costume designer, Van Broughton Ramsey ; music by Emilio Aragon ; casting by Ed Johnston.
Robert Duvall, Jeremy Irvine, Angie Cepeda, Luis Tosar, Joaquin Cosio, Javier Gutierrez.
Not rated.
DVD ; NTSC, region 1 ; Widescreen (2.39:1) presentation; 5.1 Dolby Digital.
Keywords: Older men -- Drama; Grandfathers -- Drama; Ranchers -- Texas -- Drama; Criminals -- Mexico -- Drama; Action and adventure films; Crime films; Drama; Feature films; Fiction films; Western films